Ownership structure trend among Malaysian listed companies - Mohd Adi, Mohd Nazir; Wan Yusoff, Wan Fauziah; Abdul Samad, Abdul Kader Omer (American Scientific Publishers, 2018)
Over the past two decades, the issues of ownership structure and corporate governance have been extensively addressed in previous research. In emerging markets including Malaysia, these issues have attracted the public attention since the Asian financial crisis in 1997/1998. It was argued that a weak corporate governance in Malaysia during the crisis was due to the ownerships structured which too much on concentrated ownership, extensive involvement of owners in management, cross holdings, and pyramidal structure. This study therefore aims to measure corporate ownership structure among listed companies in Malaysia by drawing on the three substantial ownership structures i.e., government and nominee ownership plus foreign ownership. The study relied entirely on secondary data of 341 Malaysian listed companies that exist for throughout the periods of 2003 to 2013. The data was then analyzed using descriptive statistics including mean and standard deviation. The study discovered that ownership structure showed a general downward trend in government ownership from the year 2006. Similarly, the general trend of the mean average percentage of local nominee ownership over the 11-year period %. However, it was not a consistent decline; the local nominee ownership mean average fluctuated slightly throughout the years. Foreign nominee ownership mean average percentage of total ownership, however, increased steadily from 4.6% in 2003 to 6% in 2013, a rise by about 30.4%. The findings imply that the corporate ownerships structures trend in Malaysia become more diverse especially by the declining of government ownerships.